Leadership, creativity and innovation: a meta-analytic review. Issue 1 (2nd January 2020) - Lee, Allan; Legood, Alison; Hughes, David; Tian, Amy Wei; Newman, Alexander; Knight, Caroline
ABSTRACT: This paper reports the most comprehensive meta-analytic examination of the relationship between leadership and both followers' creative and innovative performance. Specifically, we examined 13 leadership variables (transformational, transactional, ethical, humble, leader-member exchange, benevolent, authoritarian, entrepreneurial, authentic, servant, empowering, supportive, and destructive) using data from 266 studies. In addition to providing robustly estimated correlations, we explore two theoretically and pragmatically important issues: the relative importance of the different leadership constructs and moderators of the relationship between leadership and employee creativity and innovation. Regrading creative performance, authentic, empowering, and entrepreneurial leadership demonstrated the strongest relationships. For innovative performance, both transactional (contingent reward) and supportive leadership appear particularly relevant. The current study synthesizes an important, burgeoning, diverse body of research, and in doing so, generates nuanced evidence that can be used to guide theoretical advancements, improved research designs, and up-to-date policy recommendations regarding leading for creativity, and innovation.